PENGGUNAAN DANA DESA SESUAI DENGAN PERMENDES NOMOR 22 TAHUN 2016 DI KECAMATAN SAMBELIA TAHUN 2017 - I GUSTI NGURAH ARYAWAN ASASANDI (GANEC SWARA, 2018)
Village funds have begun to be disbursed in 2015 with an allocation of around 20 (Twenty) Trillion Rupiahs throughout Indonesia and crept up in 2016 to be 40 (Forty) Trillion Rupiahs and lastly in 2017 to 60 (Sixty) Three trillion Rupiahs, so the average village gets village funds transfers around 800 - 900 million per village in 2017. This is a new history for the world of rural development in Indonesia. Rapidly, villages in Indonesia have begun to move forward and show positive changes in building themselves since the enactment of the Village Law Number 6 of 2014. Sambelia Subdistrict is one of the sub-districts within the administrative area of East Lombok Regency, West Nusa Tenggara Province. With the number of villages reaching 11 (eleven) villages. In 2017 the amount of village funds that entered into Sambelia District was Rp. 9,732,506,800, - (Nine Billion Seven Hundred Thirty Two Million Five Hundred Six Thousand Eight Hundred Rupiahs). This amount is the first time in the history of rural development, that is, the funds disbursed by the central government to villages in 2017 are the biggest as long as these villages are formed.This study aims to find out the amount of village funds that go into villages in Sambelia sub-district and in what area of 2017 village funds are used the most. This research method uses descriptive method, while the source of data from this research is primary and secondary data, and data retrieval techniques are carried out by document observation and field observation. The results of the study indicate that: (1) The amount of Village Fund in 2017 that enters villages in Sambelia Subdistrict is Rp. Rp. 9,734,764,000, - (Nine Billion Seven Hundred Thirty Four Million Seven Hundred Sixty Four Thousand Rupiah). (2) The area of village development is the area that is the most to be funded by village funds which is 96.2% (percent) of the total village funds in villages in Sambelia sub-district